A STUDY ON ENTREPRENEURSHIP ATTITUDE AMONG COLLEGE STUDENTS. - Fasla N.P (International Journal of Research Science and Management, 2017)
Entrepreneurship refers to the overall course of action undertaken by an owner in starting and managing enterprise for profit. Entrepreneurship contributes the economic growth and thereby plays a vital role in the development process. Students of today’s generation are the future entrepreneurs of the country. Entrepreneurship is perceived to bring economic welfare and may contribute significantly in nation’s future wealth. Many college graduates are unable to find jobs appropriate with the degree they finished. Entrepreneurship education has been acknowledged by many organizations and even the government as a promising way to improve the work insertion of young people and at the same time, contribute to social and economic welfare. This paper studies the entrepreneurship attitude among college students..